Land Snail with Periostracal Hairs Preserved in Burmese Amber - Neubauer, Thomas A. (iScience, 2019)
Excellently preserved fossils often provide important insights into evolutionary histories and adaptations to environmental change in Earth's biogeologic record. Mid-Cretaceous Burmese amber, for example, is a proven reservoir for spectacular findings. Here we document the first record of a fossil land snail with periostracal hairs preserved in amber. We interpret the development of hairs as an adaptation to the tropical forest environment, serving as a mechanism to increase adhesion of the snail to plants during foraging while collecting and transporting seeds in the process. The present record coincides with a major global radiation of angiosperms, a main food resource for terrestrial snails. As such, the expansion of flowering plants likely triggered this evolutionary adaptation and, thus, the diversification of land snails in the Cretaceous.